Genius ideas (mostly) - Pichon, Liz (London Scholastic Children's Books, 2019)
Seeing Delia without her sunglasses on is a big shock, but that's nothing compared with the surprise Dad has in store for me with his new found fitness regime. He says he's going to compete at my Sport's Day. Shame! Meanwhile Derek, Norman and I keep practicing in Dogzombies so we're really ready for the school Talent Show
English Stories
1 2 13
Keywords: Gates, Tom -- (Fictitious character) -- Juvenile fiction; Boys -- Juvenile fiction